2021
DOI: 10.1002/hyp.14166
|View full text |Cite
|
Sign up to set email alerts
|

Origin of sulphate in the unsaturated zone and groundwater of a loess aquifer

Abstract: The use of the sulphate mass balance (SMB) between precipitation and soil water as a supplementary method to estimate the diffuse recharge rate assumes that the sulphate in soil water originated entirely from atmospheric deposition; however, the origin of sulphate in soil and groundwater is often unclear, especially in loess aquifers.This study analysed the sulphur (δ 34 S-SO 4 ) and oxygen (δ 18 O-SO 4 ) isotopes of sulphate in precipitation, water-extractable soil water, and shallow groundwater samples and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The influent water in the column experiment was a mixture of several groundwater samples (the variation of water chemistry and isotopic compositions was small) reported in our other study [ 21 ]. The concentrations of SO 4 and Cl were 6.8 mg/L and 5.5 mg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The influent water in the column experiment was a mixture of several groundwater samples (the variation of water chemistry and isotopic compositions was small) reported in our other study [ 21 ]. The concentrations of SO 4 and Cl were 6.8 mg/L and 5.5 mg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The soil profile XZ1, with a depth of 55 m drilled on the Xifeng loess platform, reaches a groundwater level of 54 m and penetrates the aquifer within 1 m [ 29 ]. The water-extractable concentration of SO 4 in the soil profile XZ1 showed that SO 4 in the shallow unsaturated zone (<10 m) was mainly derived from anthropogenic sources and the dissolution of evaporite minerals, while SO 4 in the deep unsaturated zone (>10 m) was mainly derived from the dissolution of evaporite minerals [ 21 ]. In order to ensure that the experiment contained no other variables than the control variables (nature and disturbance), the soil used to fill the soil column was from the natural loess with a depth of 42.5–53 m in the soil profile XZ1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unsaturated zone (UZ) links surface water and groundwater and plays an important role in the hydrological cycle [ 32 , 33 , 34 ]. The UZ is an important site for SO 4 2− recycling and transformation and is also the main route for surface SO 4 2− pollution to enter groundwater [ 35 , 36 , 37 ]. The groundwater table is low, and the UZ is shallow in the coal mining area.…”
Section: Introductionmentioning
confidence: 99%